1976
DOI: 10.1099/00207713-26-2-180
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Yersinia enterocolitica and Yersinia pseudotuberculosis by Deoxyribonucleic Acid Hybridization and by Biochemical Reactions

Abstract: Strains of Yersinia enterocolitica and Yersinia pseudotuberculosis were characterized by deoxyribonucleic acid (DNA) hybridization, and the extent of DNA relatedness between the strains was assessed by hydroxyapatite chromatography. DNAs from 24 strains of Y . pseudotuberculosis were highly related, but Y . pseudotuberculosis was only 40 to 60% related to Y . enterocolitica. Y . enterocolitica strains formed three DNA relatedness groups, and the data strongly suggest a fourth relatedness group. Each relatednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 20 publications
3
58
0
1
Order By: Relevance
“…DNA-DNA hybridization experiments have also revealed distinct groups. Brenner et al (3) found biovars (= biotypes) 1, 2, and 3 of Knapp and Thal (15; This biochemical or DNA-DNA hybridization-related heterogeneity within Y. enterocolitica was not reflected in the fatty acid composition. For example, only minute differences, if any, in fatty acid composition could be observed between the individual biovars and the indolepositive and -negative strains as well (Table 3).…”
Section: As Shown Inmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA-DNA hybridization experiments have also revealed distinct groups. Brenner et al (3) found biovars (= biotypes) 1, 2, and 3 of Knapp and Thal (15; This biochemical or DNA-DNA hybridization-related heterogeneity within Y. enterocolitica was not reflected in the fatty acid composition. For example, only minute differences, if any, in fatty acid composition could be observed between the individual biovars and the indolepositive and -negative strains as well (Table 3).…”
Section: As Shown Inmentioning
confidence: 99%
“…pestis was analyzed, however, the taxonomic significance of this difference is questionable. Thus, the genus Yersinia appears to be homogeneous, and the fatty acid data on the yersiniae do not reflect the apparent taxonomic distance between Y. enterocolitica and Y. pseudotuberculosis as observed by DNA-DNA hybridization experiments (3,19). A reference group of five strains of Salmonella typhi was included in the study to determine the taxonomic position of Yersinia relative to another group of Enterobacteriaceae.…”
Section: As Shown Inmentioning
confidence: 99%
See 2 more Smart Citations
“…One group of sucrose-negative strains exhibits all other typical biochemical reactions of Y. enterocolitica, while the other group of sucrose-negative strains is also negative for ornithine decarboxylase, nitrate reduction, Voges-Proskauer reaction (V-P) at 37°C, ONPG, sorbose, sorbitol and trehalose . Among the rhamnose-positive strains, one group is more metabolically active at 22 than at 37°C and positive for raffinose, melibiose, a-methyl glucoside and citrate, while the other group is negative for raffinose, melibose, a-methyl glucoside or citrate (Brenner et al, 1976). Chester and Stotzky (1976) found that rhamnose-positive strains of Y. enterocolitica differed from rhamnose-negative ones in their ability to ferment raffinose and lactose, to utilize citrate and in their inability to grow on Hektoen enteric, Salmonella-Shigella or xylose-lysine deoxycholate agars.…”
Section: Isolation and Enumeration Methodsmentioning
confidence: 99%